Impact of alcohol consumption on clinical aspects of gambling disorder. (7th March 2016) - del Pino‐Gutiérrez, Amparo; Fernández‐Aranda, Fernando; Granero, Roser; Tárrega, Salomé; Valdepérez, Ana; Agüera, Zaida; Håkansson, Anders; Sauvaget, Anne; Aymamí, Neus; Gómez‐Peña, Mónica; Moragas, Laura; Baño, Marta; et al.
Abstract: Similarities between gambling disorder and substance use disorders have been extensively described. To date, however, few studies using large clinical samples have been carried out that reliably assess the relationship between different levels of alcohol consumption and gambling disorders. The present study aimed to assess the impact of baseline alcohol consumption levels on the clinical profile in a large sample of treatment‐seeking individuals. Nine hundred and fifty‐one consecutive outpatients diagnosed with gambling disorder according to DSM‐IV criteria were compared after being included in three alcohol consumption groups (low risk, abuse and risk of dependence) based on their total raw scores on the AUDIT questionnaire. Results showed a high prevalence of risk of alcohol dependence in GD patients who were immigrants, unemployed, and had a low level of education. A positive linear trend was also found between alcohol consumption level and the prevalence of other current and life‐time comorbid mental disorders, and for the presence of drug abuse. Statistically significant differences were found between the three alcohol consumption groups in terms of the evolution and severity of the gambling disorder, self‐directedness personality trait, and levels of general psychopathology, hostility and paranoid ideation. In conclusion, the results showed an association between increased alcohol consumption and greater dysfunction.